Roles of Intramolecular and Intermolecular Hydrogen Bonding in a Three-Water-Assisted Mechanism of Succinimide Formation from Aspartic Acid Residues - Takahashi, Ohgi (Molecules, 2014)
Aspartic acid (Asp) residues in peptides and proteins are prone to isomerization to the β-form and racemization via a five-membered succinimide intermediate. These nonenzymatic reactions have relevance to aging and age-related diseases. In this paper, we report a three water molecule-assisted, six-step mechanism for the formation of succinimide from Asp residues found by density functional theory calculations. The first two steps constitute a stepwise iminolization of the C-terminal amide group. This iminolization involves a quintuple proton transfer along intramolecular and intermolecular hydrogen bonds formed by the C-terminal amide group, the side-chain carboxyl group, and the three water molecules. After a conformational change (which breaks the intramolecular hydrogen bond involving the iminol nitrogen) and a reorganization of water molecules, the iminol nitrogen nucleophilically attacks the carboxyl carbon of the Asp side chain to form a five-membered ring. This cyclization is accompanied by a triple proton transfer involving two water molecules, so that a gem-diol tetrahedral intermediate is formed. The last step is dehydration of the gem-diol group catalyzed by one water molecule, and this is the rate-determining step. The calculated overall activation barrier (26.7 kcal mol(−1)) agrees well with an experimental activation energy.